KANDUNGAN GULA BUAH NANAS MADU (Ananas comosus L.merr) PADA TINGKAT KEMATANGAN YANG BERBEDA - Condro, Novita; Stefanie, Selmi Y (DINAMIS, 2022)
Honey pineapple is a type of pineapple that is favored by people in Papua. Its small shape but sweet taste is the advantage of this honey pineapple. The pineapple variety that is generally cultivated in Papua is the Smooth cayenne type. In Papua, honey pineapple is better known as wamena pineapple. The maturity of the fruit is very easy to affect the freshness of the fruit, mechanical damage and the nutritional content of the fruit contained in it. Generally, farmers prefer to harvest pineapple fruits that are still unripe and then muffled. Therefore, this study was conducted to determine the effect of the maturity level of honey pineapple fruit in Jayapura on vitamin C levels and sugar levels. From the results of the study, it was shown that the pineapple fruit of tree ripe honey contains sugar cof 12% while in pineapple honey peram sugar content of 10%.